Aza[6]helicene Platinum Complexes: Chirality Control of cis–trans Isomerism1. Issue 23 (17th April 2014) - Mendola, Daniele; Saleh, Nidal; Vanthuyne, Nicolas; Roussel, Christian; Toupet, Loïc; Castiglione, Franca; Caronna, Tullio; Mele, Andrea; Crassous, Jeanne
Abstract It was serendipitously observed that cis‐[PtCl2(NCEt)PPh3] reacted differently with either racemic or enantiopure 4‐aza[6]helicene, giving respectively cis (racemic) and trans (enantiopure) [PtIICl2(4‐aza[6]helicene)PPh3] complexes. This unexpected reactivity is explained through a dynamic process (crystallization‐induced diastereoselective transformation) and enables a new aspect of reactivity in chiral transition‐metal complexes to be addressed.